Stay Home: Role of Physical Exercise Training in Elderly Individuals’ Ability to Face the COVID-19 Infection - Walid Kamal Abdelbasset (Journal of Immunology Research)
Recently, the novel coronavirus epidemic occurred in China and spread worldwide to become a global pandemic. COVID-19 is a fatal viral infection causing death, particularly in aged individuals, due to impaired immunity. To date, no intervention is available to prevent COVID-19 and its manifestations. Physical exercise training generally has health benefits, and it assists in the prevention of several chronic diseases. Therefore, this review is aimed at exploring the role of physical exercise training in the face of COVID-19 in older adults and elderly individuals. From this point of view, this review suggests that physical exercise training plays a key role in promoting immune system regulation, delaying immunity dysfunction, reducing circulatory inflammation markers, and preventing sarcopenia and thus could prevent the risk of acquiring COVID-19 infection and reduce the complications of recommended self-isolation in older adults and elderly individuals. Additionally, immunity biomarkers were optimistically demonstrated in older adults following physical exercise training, thereby reducing mortality and morbidity rates. Finally, in accordance with recommendations to stay home and perform self-isolation to prevent the spread of COVID-19, all populations are strongly recommended to practice regular home exercise training at home to promote immune system functioning.